PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUKMENINGKATKAN HASIL BELAJAR IPSSISWA KELAS IV SDN 52DURI BARAT KECAMATAN MANDAU - Nike Rusfianti; Erlisnawati Erlisnawati; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the student achievement of social studies fourth graderes SDN 52 Duri Barat still low with an average value of 61,5 and minimum completenness criteria (KKM) social studies is 65. Between students, amounting to 20 people only 6 students who achieve classical KKM with 30%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of cooperative learning model type Think Pair Share (TPS) can improve students achievment of social studies at SDN 52 Duri Barat. The research was conducted on march 18, 2015 to april 17, 2015 by 2 cyclees. Subjects were students of SDN 52 Duri Barat, totalling 20 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained results koopertif TPS type of activity the teacher in the lerning process in cycle I frist meeting was 62,5% and at the second meeting of teacher activity increased by 8,33% to 70,83%. cycle II first meeting and the second meeting of activity increased by 16,67% to 87,5% and the second meeting of activity increased by 4,1% to 91,6%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 62,5% and at second meeting of activity increased 12,5% to 75%% and a second meeting of activity increased 8,3% improve to 83,33%. At the first meeting of the second meeting of activity increased 8,27% to 91,6%%.This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 61,5. In the first cycle improve an average of 64 with increase as 4,06% and an impove in the second with an average of 87,5 with increase as 42,27%. Result in the research that the implementation of cooperative learning model of Think Pair Share (TPS) can improve students achievement of social Studies at fourth graderes SDN 52 Duri Barat Kecamatan Mandau.Key Words : Model Learning Think Pair Share (TPS), Social Studies Achievement.